VEGF‐A165b protects against proteinuria in a mouse model with progressive depletion of all endogenous VEGF‐A splice isoforms from the kidney. (3rd July 2017) - Stevens, Megan; Neal, Christopher R.; Salmon, Andrew H. J.; Bates, David O.; Harper, Steven J.; Oltean, Sebastian
Abstract : Key points: Progressive depletion of all vascular endothelial growth factor A (VEGF‐A) splice isoforms from the kidney results in proteinuria and increased glomerular water permeability, which are both rescued by over‐expression of VEGF‐A165 b only. VEGF‐A165 b rescues the increase in glomerular basement membrane and podocyte slit width, as well as the decrease in sub‐podocyte space coverage, produced by VEGF‐A depletion. VEGF‐A165 b restores the expression of platelet endothelial cell adhesion molecule in glomerular endothelial cells and glomerular capillary circumference. VEGF‐A165 b has opposite effects to VEGF‐A165 on the expression of genes involved in endothelial cell migration and proliferation. Abstract: Chronic kidney disease is strongly associated with a decrease in the expression of vascular endothelial growth factor A (VEGF‐A). However, little is known about the contribution of VEGF‐A splice isoforms to kidney physiology and pathology. Previous studies suggest that the splice isoform VEGF‐A165 b (resulting from alternative usage of a 3′ splice site in the terminal exon) is protective for kidney function. In the present study, we show, in a quad‐transgenic model, that over‐expression of VEGF‐A165 b alone is sufficient to rescue the increase in proteinuria, as well as glomerular water permeability, in the context of progressive depletion of all VEGF‐A isoforms from the podocytes. Ultrastructural studies show that the glomerular basement membrane is thickened, podocyte slit width is increased and sub‐podocyte space coverage is reduced when VEGF‐A is depleted, all of which are rescued in VEGF‐A165 b over‐expressors. VEGF‐A165 b restores the expression of platelet endothelial cell adhesion molecule‐1 in glomerular endothelial cells and glomerular capillary circumference. Mechanistically, it increases VEGF receptor 2 expression both in vivo and in vitro and down‐regulates genes involved in migration and proliferation of endothelial cells, otherwise up‐regulated by the canonical isoform VEGF‐A165 . The results of the present study indicate that manipulation of VEGF‐A splice isoforms could be a novel therapeutic avenue in chronic glomerular disease. Key points: Progressive depletion of all vascular endothelial growth factor A (VEGF‐A) splice isoforms from the kidney results in proteinuria and increased glomerular water permeability, which are both rescued by over‐expression of VEGF‐A165 b only. VEGF‐A165 b rescues the increase in glomerular basement membrane and podocyte slit width, as well as the decrease in sub‐podocyte space coverage, produced by VEGF‐A depletion. VEGF‐A165 b restores the expression of platelet endothelial cell adhesion molecule in glomerular endothelial cells and glomerular capillary circumference. VEGF‐A165 b has opposite effects to VEGF‐A165 on the expression of genes involved in endothelial cell migration and proliferation.